Method of analysis of speed, stroke rate and stroke distance in aquatic loco-motions - Kleshnev, V. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
A method was developed for assessment of speed (V) and stroke distance (SD) at various stroke rates (R) during aquatic locomotion. The method is based on the equation Fd = k V2, which describes dependence of hydrodynamic drag force Fd on V in water. Equality of the effective mechanical work per stroke (EWS) at various stroke rates was taken as a criterion for assessment. Two equations were developed for calculation of -model- speed Vm = V0 (R1/R0)1/3 and SDm = SD0 (R0/R1)2/3. This method was verified using the data of biomechanical measurements in rowing, when mechanical work per stroke was measured directly. A high correlation was found (r=0.81, p<0.001) between deviations of the actual V and SD values to -models- and deviations of EWS from average. The method can be used in step-test and race analysis in swimming, rowing and canoeing.